Causes of fevers and diagnostic strategies among the HIV patients hospitalized in the regional hospital of Comè (southern Benin) : the National Study. - Agbodande K.A., K.A.; Attinsounon, C.A; Wanvoegbe, F.A; Azon- Kouanou, A.; Kpossou, A.R.; Zannou, D.M; Houngbe, F (My University, 2015)
Over the past decade, considerable progress has been achieved in expanding the access towards antiretroviral therapy (ART) in developing countries against AIDS, however Sub-Saharan Africa continues to record the highest number of deaths related to HIV. A cross-sectional, descriptive and analytical study was conducted in the department of polyvalent medicine of the first referral hospital of Comè over a two-year-period, from 1st January 2012 to 31st December 2013 to determine the cause of fever among the HIV patients. A total of 87 HIV infected patients were hospitalized during the study period. Among them, there were 60 cases of fever (69.0%). The mean age was 39.4 ± 11.3 years old and the sex ratio (M / F) was 0.94. Acute fever was recorded in 41.7% of cases and long term fever in 58.3% of cases. Infectious diseases like diarrhoea, pneumonia, oro - pharyngeal candidiasis, tuberculosis and cerebral toxoplasmosis were the main causes of fever in hospitalized HIV patients (96.3%).
Keywords: Causes of fevers and diagnostic strategies among the HIV patients hospitalized in the regional hospital of Comè (southern Benin) : the National Study.